Randomized Phase II Trial of Proton Craniospinal Irradiation Versus Photon Involved-Field Radiotherapy for Patients With Solid Tumor Leptomeningeal Metastasis. Issue 33 (20th November 2022) - Yang, Jonathan T.; Wijetunga, N. Ari; Pentsova, Elena; Wolden, Suzanne; Young, Robert J.; Correa, Denise; Zhang, Zhigang; Zheng, Junting; Steckler, Alexa; Bucwinska, Weronika; Bernstein, Ashley; Betof Warner, Allison; et al.
Abstract : PURPOSE: Photon involved-field radiotherapy (IFRT) is the standard-of-care radiotherapy for patients with leptomeningeal metastasis (LM) from solid tumors. We tested whether proton craniospinal irradiation (pCSI) encompassing the entire CNS would result in superior CNS progression-free survival (PFS) compared with IFRT. PATIENTS AND METHODS: We conducted a randomized, phase II trial of pCSI versus IFRT in patients with non–small-cell lung cancer and breast cancers with LM. We enrolled patients with other solid tumors to an exploratory pCSI group. For the randomized groups, patients were assigned (2:1), stratified by histology and systemic disease status, to pCSI or IFRT. The primary end point was CNS PFS. Secondary end points included overall survival (OS) and treatment-related adverse events (TAEs). RESULTS: Between April 16, 2020, and October 11, 2021, 42 and 21 patients were randomly assigned to pCSI and IFRT, respectively. At planned interim analysis, a significant benefit in CNS PFS was observed with pCSI (median 7.5 months; 95% CI, 6.6 months to not reached) compared with IFRT (2.3 months; 95% CI, 1.2 to 5.8 months; P < .001). We also observed OS benefit with pCSI (9.9 months; 95% CI, 7.5 months to not reached) versus IFRT (6.0 months; 95% CI, 3.9 months to not reached; P = .029). There was no difference in the rate of grade 3 and 4 TAEs ( P = .19). In the exploratory pCSI group, 35 patients enrolled, the median CNS PFS was 5.8 months (95% CI, 4.4 to 9.1 months) and OS was 6.6 months (95% CI, 5.4 to 11 months). CONCLUSION: Compared with photon IFRT, we found pCSI improved CNS PFS and OS for patients with non–small-cell lung cancer and breast cancer with LM with no increase in serious TAEs.